2002
DOI: 10.1007/s726-002-8202-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, electrochemical and spectral properties of some ω-N-quinonyl amino acids

Abstract: Four series of omega-N-quinonyl amino acids were synthesized by Michael-like additions. The quinones include 2-phenylthio-1,4-benzoquinone, 1,4-naphthoquinone, 2-methyl-1,4-naphthoquinone and 2,3-dichloro-1,4-naphthoquinone. These modified amino acids can be used for post chain assembly modifications of biologically active peptides, which target the quinonic drug to a cancer damaged area. The electron-transfer capabilities of the modified amino acids were probed by cyclic voltammetry measurements. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
(17 reference statements)
1
21
2
Order By: Relevance
“…This is in contrast with the behaviour recorded in non-aqueous aprotic solvent, in which NQ1 displays three reduction waves, two of them being irreversible [34]. A decomposition of the compound was suggested to explain the nonreversibility of the first reduction process and the appearance of a third wave [34]. The formal redox potential, E°' = À0.420 V (vs. SCE), is in good agreement with the values reported for other structurally close 2-amino-1,4-naphthoquinones, ranging between À0.419 and À0.476 V (vs. SCE, at pH 7) [37] depending on the investigated compound.…”
Section: Behaviour In Buffered Solutioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This is in contrast with the behaviour recorded in non-aqueous aprotic solvent, in which NQ1 displays three reduction waves, two of them being irreversible [34]. A decomposition of the compound was suggested to explain the nonreversibility of the first reduction process and the appearance of a third wave [34]. The formal redox potential, E°' = À0.420 V (vs. SCE), is in good agreement with the values reported for other structurally close 2-amino-1,4-naphthoquinones, ranging between À0.419 and À0.476 V (vs. SCE, at pH 7) [37] depending on the investigated compound.…”
Section: Behaviour In Buffered Solutioncontrasting
confidence: 95%
“…This is in contrast with the behaviour recorded in non-aqueous aprotic solvent, in which NQ1 displays three reduction waves, two of them being irreversible [34]. A decomposition of the compound was suggested to explain the nonreversibility of the first reduction process and the appearance of a third wave [34].…”
Section: Behaviour In Buffered Solutioncontrasting
confidence: 73%
“…This reaction would involve loss of the 15 N-1 H cross peak for G1. The Michael reaction is well known to occur between primary amines and quinones at near neutral pH (Bittner et al, 2002;Sridhar et al, 2001) or ␣,␤ unsaturated ketones and involves a 1,4 addition as shown in Figure 3 for the case of quinones. We can find no reports of amide nitrogens reacting in this manner.…”
Section: Shown Inmentioning
confidence: 99%
“…However, the ratio of the current amplitudes between the two reduction processes is not equal to unity because of fast disproportionation of the anion radical, making the ratio usually greater than unity in favor of the first redox couple, depending on scan rate. 19 As mentioned above, calixarene derivatives are widely used in supramolecular chemistry for the construction of various receptors for charged or neutral guest molecules. Such host -guest interaction can be controlled and detected electrochemically when organic, organometallic or inorganic redox-active centers are incorporated into calix[4]-arene framework.…”
Section: Electrochemical Properties By Cyclic Voltammetrymentioning
confidence: 99%